Assessment of Renal Function; Clearance, the Renal Microcirculation, Renal Blood Flow, and Metabolic Balance. Issue 1 (January 2013) - Beierwaltes, William H.; Harrison‐Bernard, Lisa M.; Sullivan, Jennifer C.; Mattson, David L.
Abstract: Historically, tools to assess renal function have been developed to investigate the physiology of the kidney in an experimental setting, and certain of these techniques have utility in evaluating renal function in the clinical setting. The following work will survey a spectrum of these tools, their applications and limitations in four general sections. The first is clearance, including evaluation of exogenous and endogenous markers for determining glomerular filtration rate, the adaptation of estimated glomerular filtration rate in the clinical arena, and additional clearance techniques to assess various other parameters of renal function. The second section deals with in vivo and in vitro approaches to the study of the renal microvasculature. This section surveys a number of experimental techniques including corticotomy, the hydronephrotic kidney, vascular casting, intravital charge coupled device videomicroscopy, multiphoton fluorescent microscopy, synchrotron‐based angiography, laser speckle contrast imaging, isolated renal microvessels, and the perfused juxtamedullary nephron microvasculature. The third section addresses in vivo and in vitro approaches to the study of renal blood flow. These include ultrasonic flowmetry, laser‐Doppler flowmetry, magnetic resonance imaging (MRI), phase contrast MRI, cine phase contrast MRI, dynamic contrast‐enhanced MRI, blood oxygen level dependent MRI, arterial spin labeling MRI, x‐ray computed tomography, and positron emission tomography. The final section addresses the methodologies of metabolic balance studies. These are described for humans, large experimental animals as well as for rodents. Overall, the various in vitro and in vivo topics and applications to evaluate renal function should provide a guide for the investigator or physician to understand and to implement the techniques in the laboratory or clinic setting. © 2013 American Physiological Society. Compr Physiol 3:165‐200, 2013.